Comparison of Multi-Drug Resistant Environmental Methicillin-Resistant Staphylococcus aureus Isolated from Recreational Beaches and High Touch Surfaces in Built Environments - Roberts, Marilyn C.; Soge, Olusegun O.; No, David (Frontiers in Microbiology, 2013)
Over the last decade community-acquired methicillin-resistant Staphylococcus aureus [MRSA] has emerged as a major cause of disease in the general population with no health care exposure or known classical risk factors for MRSA infections. The potential community reservoirs have not been well defined though certain strains such as ST398 and USA300 have been well studied in some settings. MRSA has been isolated from recreational beaches, high-touch surfaces in homes, universities and other community environmental surfaces. However, in most cases the strains were not characterized to determine if they are related to community-acquired or hospital-acquired clinical strains. We compared 55 environmental MRSA from 805 samples including sand, fresh and marine water samples from local marine and fresh water recreational beaches (n=296), high touch surfaces on the University of Washington campus (n=294), surfaces in UW undergraduate housing (n=85), and the local community (n=130). Eleven USA300, representing 20% of the isolates, were found on the UW campus surfaces, student housing surfaces and on the community surfaces but not in the recreational beach samples from the Northwest USA. Similarly, the predominant animal ST133 was found in the recreational beach samples but not in the high touch surface samples. All USA300 isolates were multi-drug resistant carrying 2-6 different antibiotic resistance genes coding for kanamycin, macrolides and/or macrolides-lincosamides-streptogramin B and tetracycline, with the majority [72%] carrying 4-6 different antibiotic resistance genes. A surprising 98% of the 55 MRSA isolates were resistant to other classes of antibiotics and most likely represent reservoirs for these genes in the environment.